Think with me, or think for me? On the future role of artificial intelligence in marketing strategy formulation. Issue 4 (22nd April 2020) - Eriksson, Theresa; Bigi, Alessandro; Bonera, Michelle
Abstract : Purpose: This paper explores if and how Artificial Intelligence can contribute to marketing strategy formulation. Design/methodology/approach: Qualitative research based on exploratory in-depth interviews with industry experts currently working with artificial intelligence tools. Findings: Key themes include: (1) Importance of AI in strategic marketing decision management; (2) Presence of AI in strategic decision management; (3) Role of AI in strategic decision management; (4) Importance of business culture for the use of AI; (5) Impact of AI on the business' organizational model. A key consideration is a "creative-possibility perspective, " highlighting the future potential to use AI not only for rational but also for creative thinking purposes. Research limitations/implications: This work is focused only on strategy creation as a deliberate process. For this, AI can be used as an effective response to the external contingencies of high volumes of data and uncertain environmental conditions, as well as being an effective response to the external contingencies of limited managerial cognition. A key future consideration is a "creative-possibility perspective." Practical implications: A practical extension of the Gartner Analytics Ascendancy Model (Maoz, 2013). Originality/value: This paper aims to contribute knowledge relating to the role of AI in marketing strategy formulation and explores the potential avenues for future use of AI in the strategic marketing process. This is explored through the lens of contingency theory, and additionally, findings are expressed using the Gartner analytics ascendancy model.